Resilience for all Striving for Equity Through Community-Driven Design - Wilson, Barbara (Island Press/Center for Resource Economics, 2018)
In the United States, people of color are disproportionally more likely to live in environments with poor air quality, in close proximity to toxic waste, and in locations more vulnerable to climate change and extreme weather events. In many vulnerable neighborhoods, structural racism and classism prevent residents from having a seat at the table when decisions are made about their community. In an effort to overcome power imbalances and ensure local knowledge informs decision-making, a new approach to community engagement is essential. In Resilience for All, Barbara Brown Wilson looks at less conventional, but often more effective methods to make communities more resilient. She takes an in-depth look at what equitable, positive change through community-driven design looks like in four communities-East Biloxi, Mississippi; the Lower East Side of Manhattan; the Denby neighborhood in Detroit, Michigan; and the Cully neighborhood in Portland, Oregon. These vulnerable communities have prevailed in spite of serious urban stressors such as climate change, gentrification, and disinvestment. Wilson looks at how the lessons in the case studies and other examples might more broadly inform future practice. She shows how community-driven design projects in underserved neighborhoods can not only change the built world, but also provide opportunities for residents to build their own capacities. .